Functional and Evolutionary Analyses Identify Proteolysis as a General Mechanism for NLRP1 Inflammasome Activation. - Joseph Chavarría-Smith; Patrick S Mitchell; Alvin M Ho; Matthew D Daugherty; Russell E Vance (PLoS Pathogens, 2016)
Inflammasomes are cytosolic multi-protein complexes that initiate immune responses to infection by recruiting and activating the Caspase-1 protease. Human NLRP1 was the first protein shown to form an inflammasome, but its physiological mechanism of activation remains unknown. Recently, specific variants of mouse and rat NLRP1 were found to be activated upon N-terminal cleavage by the anthrax lethal factor protease. However, agonists for other NLRP1 variants, including human NLRP1, are not known, and it remains unclear if they are also activated by proteolysis. Here we demonstrate that two mouse NLRP1 paralogs (NLRP1AB6 and NLRP1BB6) are also activated by N-terminal proteolytic cleavage. We also demonstrate that proteolysis within a specific N-terminal linker region is sufficient to activate human NLRP1. Evolutionary analysis of primate NLRP1 shows the linker/cleavage region has evolved under positive selection, indicative of pathogen-induced selective pressure. Collectively, these results identify proteolysis as a general mechanism of NLRP1 inflammasome activation that appears to be contributing to the rapid evolution of NLRP1 in rodents and primates.